1979
DOI: 10.1111/j.1532-5415.1979.tb01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's Disease: Current Concepts of Therapy*

Abstract: Huntington's disease (Huntington's chorea), a degenerative disorder of the central nervous system, is inherited in an autosomal dominant pattern. Since there is no cure for this genetic disorder, therapy has been focused on pharmacologic manipulation of the involved neurotransmitter systems. In Huntington's disease, there is a functional predominance of striatal dopaminergic activity over antagonist cholinergic and possibly GABA-minergic systems. Many dopaminergic antagonists and cholinergic and GABA-minergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Dopa decarboxylase activity was elevated in the erythrocytes of HD patients compared to the control group [31]. However, Butterfield et al suggested that changes in dopa decarboxylase activity in HD patients could be connected to phenothiazines used often in therapy [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Dopa decarboxylase activity was elevated in the erythrocytes of HD patients compared to the control group [31]. However, Butterfield et al suggested that changes in dopa decarboxylase activity in HD patients could be connected to phenothiazines used often in therapy [31,32].…”
Section: Discussionmentioning
confidence: 99%